Exploring the relationship between strength and flexibility in middle-aged adults / Wan Mohd Syafiq ... [et al.]. - Syafiq, Wan Mohd; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Haziq, Amrun; Md Yusoff, Yusandra (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Hand-grip strength and flexibility are key markers of physical health in middle-aged adults. Despite their importance, limited research explores their correlation, especially in diverse populations and real-world settings. This study addresses gaps by examining their interrelationship and potential combined impact on health outcomes, contributing to a deeper understanding of functional independence and aging. A stratified random sample of 23 middle-aged adults (40–60 years) was selected at UiTM Seremban 3. Hand-grip strength was measured using a digital dynamometer, while flexibility was assessed with the sit-and-reach test. Pearson’s and Spearman’s correlation analyses were conducted to determine the relationship between hand-grip strength and flexibility.